2021
DOI: 10.1039/d0nj04721j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide as a pesticide carrier for enhancing fungicide activity against Magnaporthe oryzae

Abstract: GO can cause the cell damage by cutting cell wall and oxidative stress, and the drug absorbed on the surface of GO were released precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This graphene transport pathway was highly dependent on the growth of root hairs, which could be regulated by modifying the culture medium. The regulable internalization of graphene materials offers methods for the feasible delivery of a certain amount of specific pesticides, 44 fungicides, 45 or antimicrobials 46 to plants using graphene as the delivery matrix. The confirmation of the transport pathway will contribute to the potential application of nanomaterials in agriculture as the targeting carrier.…”
Section: Accumulation Of Graphene In Rootsmentioning
confidence: 99%
“…This graphene transport pathway was highly dependent on the growth of root hairs, which could be regulated by modifying the culture medium. The regulable internalization of graphene materials offers methods for the feasible delivery of a certain amount of specific pesticides, 44 fungicides, 45 or antimicrobials 46 to plants using graphene as the delivery matrix. The confirmation of the transport pathway will contribute to the potential application of nanomaterials in agriculture as the targeting carrier.…”
Section: Accumulation Of Graphene In Rootsmentioning
confidence: 99%
“…GO can disrupt mycelia and threaten cell integrity, and can impair glutathione (GSH) on the cell membrane via electron transfer what results in reduced activity of fungal cells. Moreover, in greenhouse experiments this nanocomposite considerably reduced the severity of rice blast [ 202 ]. GO−polydopamine nanocomposite loaded with hymexazol showed NIR-laser-dependent and pH-dependent release of this fungicide as well as higher adhesion performance and persistence than the solution of hymexazol fungicide after a simulated-rainwash experiment, exhibiting antifungal activity against F. oxysporum f. sp.…”
Section: Applications Against Plant Patogenic Microorganismsmentioning
confidence: 99%
“…colleagues used Cu 2−x Se-modified GO as a vector for chlorpyrifos and found that this PDS exhibited excellent drift resistance, pH-responsive and photothermally responsive sustained release, and enhanced antipest activity. 20 Shen's group reported a PEG-modified GO as a carrier for emamectin benzoate (EB) and found that after loading on PEG-GO, the EB@PEG-GO had a significantly improved dispersion stability in water, pH-responsive sustained release, enhanced anti-UV properties, a prolonged persistent period, and sustainable antipest activity. 16 In another report, Zhou et al used GO as a carrier for acaricides (avermectin, bifenazate, etoxazole, and spirodiclofen) delivery and found that the GO-based PDS exhibited significantly enhanced efficiency against acaricides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nanomaterials-based multifunctional pesticide delivery system (PDS) has drawn great interest in pesticide formulation innovation. − Various nanomaterials including graphene oxide (GO), mesoporous silicon, porous calcium carbonate, a metal organic framework (MOF), MXene, and polymeric micelles are employed as vectors for pesticide delivery. − Among them, GO is considered to be a suitable candidate for pesticide delivery due to its huge surface area, high drug-loading performance, good stability, and excellent biocompatibility. − As a potential 2D nanomaterial, GO has had broad applications in drug delivery and biomedicine during the past decade, which can provide beneficial guidance for its innovation in PDS. − In recent years, researchers have gradually expanding the application of GO in pesticide delivery and plant protection. For instance, Sharma and colleagues used Cu 2– x Se-modified GO as a vector for chlorpyrifos and found that this PDS exhibited excellent drift resistance, pH-responsive and photothermally responsive sustained release, and enhanced antipest activity . Shen’s group reported a PEG-modified GO as a carrier for emamectin benzoate (EB) and found that after loading on PEG-GO, the EB@PEG-GO had a significantly improved dispersion stability in water, pH-responsive sustained release, enhanced anti-UV properties, a prolonged persistent period, and sustainable antipest activity .…”
Section: Introductionmentioning
confidence: 99%